External debt and capital flight in sub-Saharan Africa: The role of institutions - (:unkn) unknown (My University, 2023)
This paper aims to study the impact of external debt on capital flight conditional on the institutional quality of host countries. Three major contributions emerge. First, the role of external debt in capital flight is clarified. Econometric results based on 26 sub-Saharan African countries over the period 1970-2015 show a positive relationship between external debt and capital flight. Second, high quality institutions weaken the link between debt and capital flight somewhat, although they do not eliminate it completely. The results suggest that improving the quality of institutions in sub-Saharan African countries could help minimise the contribution of external debt to capital flight. Third, the analysis takes into account panel data, the persistence of capital flight and the potential endogeneity of the regressors.
Keywords: African Research